In-Vivo Evaluation Of Drug-Herb Interaction Between Glibenclamide And Trigonella Foenum-Graecum By Pharmacodynamic, Pharmacokinetic And Histopathological Studies In Diabetes Mellitus Induced Rats - Amna Ali Alhadad, Dr. K. Sunita (International Journal of Advanced Science and Technology, 2020)
Traditional medications obtained from the medicated herbal plants are used by about maximum percentage of world population for different chronic disease conditions. Diabetes (Hyperglycemia- high blood sugar level) is a very important metabolic disorder in different developed and developing countries including India. It causes very serious complications on health of human beings, especially in the rural and subrural areas. Trigonella foenum-graecum (Fenugreek plant) is a well-known traditionally used medicated herb, possesses different therapeutical activities. Fenugreek leaves have been used as traditional herbal medicines not only for hyperglycemia but also in hyperlipidimia, cellulitis and gastrointestinal disorders. Preliminary animal and human trials suggested the possible antihyperglycemic activity and antihyperlipidemic activity of oral fenugreek leaf extract. T. foenum-graecum leaves have also previously been shown to have antihyperglycemic and hypocholesterolemic effects on Type I and Type II Diabetes mellitus patients and experimental induced diabetic animals. However, the research so far on the hypoglycemic effect of fenugreek couldn’t establish the optimum dose-level for experimental subjects. Hence, the research studies are required to study the pharmacodynamic and pharmacokinetic properties in order to determine the effect of fenugreek herb on the hyperglycemic patients who are taking the therapy with synthetic drugs. This study was taken up to discover the influence of Trigonella foenum-graecum on the pharmacokinetics and pharmacodynamics of Glibenclamide in rats. Results have proven the negative (decrease) effect of Trigonella foenum-graecum on pharmacokinetics but positive (increase) effect on pharmacodynamics of Glibenclamide.